Biobridge: An Outlook on Translational Bioinks for 3D Bioprinting. Issue 3 (3rd December 2021) - Gu, Yawei; Forget, Aurelien; Shastri, V. Prasad
Abstract: 3D‐bioprinting (3DBP) possesses several elements necessary to overcome the deficiencies of conventional tissue engineering, such as defining tissue shape a priori, and serves as a bridge to clinical translation. This transformative potential of 3DBP hinges on the development of the next generation of bioinks that possess attributes for clinical use. Toward this end, in addition to physicochemical characteristics essential for printing, bioinks need to possess proregenerative attributes, while enabling printing of stable structures with a defined biological function that survives implantation and evolves in vivo into functional tissue. With a focus on bioinks for extrusion‐based bioprinting, this perspective review advocates a rigorous biology‐based approach to engineering bioinks, emphasizing efficiency, reproducibility, and a streamlined translation process that places the clinical endpoint front and center. A blueprint for engineering the next generation of bioinks that satisfy the aforementioned performance criteria for various translational levels (TRL1‐5) and a characterization tool kit is presented. Abstract : 3D‐bioprinting (3DBP) is a promising technology that serves as a bridge to clinical translation. The translational potential of 3DBP depends on the development of the next generation of bioinks. Translational bioinks need to possess proregenerative attributes, while enabling printing of stable structures that survive implantation and evolve into functional tissue.